Waiting for Müteferrika - Sabev, Orlin.
1 online resource (168 pages)
Keywords: Sabev investigates the first Ottoman/Muslim printer Ibrahim Müteferrika and his printing activity in the first half of the 18th century. By focusing on Müteferrika's western-formed mind-set, the book analyzes the influence of his printing enterprise on the transition from scribal tradition to print culture in the Ottoman Turkish/Muslim milieu.